2002
DOI: 10.1148/radiol.2251011477
|View full text |Cite
|
Sign up to set email alerts
|

Renal Angiomyolipoma: Relationships between Tumor Size, Aneurysm Formation, and Rupture

Abstract: Aneurysm formation appears to be related to tumor size, and large aneurysms confer a higher probability of rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
262
1
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(280 citation statements)
references
References 18 publications
4
262
1
13
Order By: Relevance
“…The characteristic feature of renal AML is thick-walled blood vessels, which do not have normal elastin and are prone to rupture (11). Aneurysm size (close to 5 mm) and tumor size (close to 4 cm) significantly account for rupture and hemorrhage (12). Likewise, another study revealed that tumors with serial changes in volumes were associated with higher probability of hemorrhagic lesions (13).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristic feature of renal AML is thick-walled blood vessels, which do not have normal elastin and are prone to rupture (11). Aneurysm size (close to 5 mm) and tumor size (close to 4 cm) significantly account for rupture and hemorrhage (12). Likewise, another study revealed that tumors with serial changes in volumes were associated with higher probability of hemorrhagic lesions (13).…”
Section: Methodsmentioning
confidence: 99%
“…The hemorrhage risk of renal angiomyolipomas in TSC patients is between 25 and 50% [18,19] , and between 20-30% of pa- tients with hemorrhages present to the emergency room in shock [20] . The hemorrhage risk is significantly increased for aneurysms larger than 5 mm [21] .…”
Section: Renal Angiomyolipomas In Tscmentioning
confidence: 99%
“…Yamakado et al reported a significant positive association between aneurysm formation and active retroperitoneal hemorrhage. 29 There may be a role for angiography, either conventional renal angiography or renal CTA, in informing treatment decisions, particularly in smaller, asymptomatic angiomyolipoma where surveillance may be considered.…”
Section: Selecting Patients Who May Benefit From Treatmentmentioning
confidence: 99%